Broncalt®, class II medical device, in patients with chronic upper airways disease: a survey in clinical practice - Cupido, Gian Franco; Gelardi, Matteo; La Mantia, Ignazio; Aragona, Salvo Emanuele; Vicini, Claudio; Ciprandi, Giorgio; otorhinolaryngological disorders, Italian Study Group on inflammatory (Acta Biomedica Atenei Parmensis, 2019)
Inflammation and infection are common pathogenic mechanisms involved in many otorhinolaryngological (ORL) chronic diseases. Broncalt® is a class II Medical Device containing: thermal water (Medesano, PR, Italy), hyaluronic acid, and grapefruit seed extract. It could exert a safe and effective anti-inflammatory, washing, and antimicrobial activity by virtue of these components. Therefore, the aim of the current survey, conducted in clinical practice of 84 Italian ORL centers, was to evaluate its safety and efficacy in the treatment of patients with chronic upper airways disease. The 1,817 (958 males, mean age 49 years) patients were evaluated at baseline (T0) and after one (T1) and two (T2) weeks of treatment, they were treated or not treated with Broncalt®. Signs and symptoms severity were measured by visual analogue scale. Broncalt® significantly, quickly, and safely diminished the clinical features in all sub-groups (p